ANALISIS FRAMING KONFLIK ISRAEL PALESTINA DALAM PEMBERITAAN MEDIA AL-JAZEERA (Fakultas Dakwah dan Komunikasi, 2020)
This study aims to describe Al Jazeera's media framing regarding the Palestinian Israeli conflict, which focuses on the population in Jerusalem which is raised in a document entitled